Bi Works as a Li Reservoir for Promoting the Fast‐Charging Performance of Phosphorus Anode for Li‐Ion Batteries. Issue 19 (27th February 2022) - Zhang, Shaojie; Zhang, Yiming; Zhang, Ziyi; Wang, Huili; Cao, Yu; Zhang, Baoshan; Liu, Xinyi; Mao, Chong; Han, Xinpeng; Gong, Haochen; Yang, Zhanxu; Sun, Jie
Abstract: Phosphorus anodes are a promising for fast‐charging high‐energy lithium‐ion batteries because of their high specific capacity (2596 mAh g –1 ) and suitable lithiation potential (0.7 V vs Li + /Li). To solve the large volumetric change and inherent poor electrical conductivity, various carbon‐based materials have been studied for loading P. However, the local aggregation of Li ions and electrons in P particles especially in the fast‐charging process induces an uneven lithiation reaction and the great transient stress, leading to poor fast‐charging performance. Herein, bismuth nanoparticles are implanted into a P/graphite (P/C) composite using ball milling. The Bi anode works as a small Li reservoir for trapping Li in the lithiation process and emitting Li in delithiation process prior to P anode, because the Bi anode has a starting lithiation/delithiation potential that is a little bit higher/lower than the P anode. Moreover, the low Li diffusion barrier in Bi and the stable interface between Bi and P enhance the Li reservoir effect of Bi, which promotes fast and uniform lithiation/delithiation reactions and avoids continuous cracking of the Bi‐P/C electrode. Therefore, the Bi‐P/C anode provides a high fast‐charging capacity of 1755.7 mAh g –1 at 7.8 A g –1 (5.2 C) and a high capacity retention of 86.3% after 300 cycles. Abstract : Bi works as a small Li reservoir for trapping/emitting Li in lithiation/delithiation processes respectively, prior to a P anode. Moreover, the low Li diffusion barrier in Bi and the stable interface between Bi and P enhance the Li reservoir effect of Bi, which promotes fast and uniform lithiation/delithiation reactions and avoids continuous cracking of Bi‐P/C electrodes.